Quality and learning curve of handheld versus stand-alone non-mydriatic cameras - Gosheva M; Klameth C; Norrenberg L; Clin L; Dietter J; Haq W; Ivanov IV; Ziemssen F; Leitritz MA (Clinical Ophthalmology, 2017)
Mariya Gosheva,1 Christian Klameth,1 Lars Norrenberg,2 Lucien Clin,3 Johannes Dietter,4 Wadood Haq,4 Iliya V Ivanov,4–6 Focke Ziemssen,1 Martin A Leitritz7 1University Eye Hospital, Centre for Ophthalmology, Tuebingen, 2Department of Obstetrics and Gynecology, Klinikum am Steinenberg, District Hospital Reutlingen, Reutlingen, 3School of Informatics, Reutlingen University, 4Division of Experimental Ophthalmology, Centre for Ophthalmology, Institute for Ophthalmic Research, 5Vision Rehabilitation Research Unit, Centre for Ophthalmology, University Eye Hospital, Eberhard Karls, 6ZEISS Vision Science Lab, Institute for Ophthalmic Research, Centre for Ophthalmology, University of Tuebingen, 7Section for Experimental Ophthalmic Surgery and Refractive Surgery, University Eye Hospital, Centre for Ophthalmology, Tuebingen, Germany Purpose: Nowadays, complex digital imaging systems allow detailed retinal imaging without dilating patients’ pupils. These so-called non-mydriatic cameras have advantages in common circumstances (eg, for screening or emergency purposes) but present limitations in terms of image quality and field of view. We compare the usefulness of two non-mydriatic camera systems (ie, a handheld versus a stand-alone device) for fundus imaging. The primary outcome was image quality. The secondary outcomes were learning effects and quality grade-influencing factors.Methods: The imaging procedures followed standard protocol and were all performed by the same investigator. Camera 1 (DRS®) was a stand-alone system, while Camera 2 (Smartscope® PRO) was a mobile system. In order to evaluate possible learning effects, we selected an examiner with no prior training in the use of these systems. The images were graded separately by two experienced and “blinded” ophthalmologists following a defined protocol.Results: In total, 211 people were enrolled. Quality grade comparisons showed significantly better grades for Camera 1. Both systems achieved better quality grades for macular images than for disc-centered images. No remarkable learning effects could be demonstrated.Conclusions: Both camera systems are useful for fundus imaging. The greater mobility of Camera 2 was associated with lower image quality. For screening scenarios or telemedicine, it must be determined whether image quality or mobility is more important. Keywords: imaging, non-mydriatic, handheld camera, learning curve